UJI ORGANOLEPTIK ANEKAUJI ORGANOLEPTIK ANEKA BAKSO SOLUSI PEMENUHAN KONSUMEN DI KECAMATAN BANYAKAN KABUPATEN KEDIRI BAKSO SEBAGAI SOLUSI PEMENUHAN HARAPAN KONSUMEN DI DESA MANYARAN KECAMATAN BANYAKAN KABUPATEN KEDIRI - Solikin, Nur; Tanjungsari, Ardina; Putra, Andri (Jurnal Agriovet, 2024)
This research aims to analyze the quality of beef meatballs and chicken meatballs through organoleptic tests. The research was conducted in Manyaran Village, Banyakan District, Kediri Regency. The research method uses experiments with 6 (six) formulas, namely (A1, A2, A3, B1, B2, B3) panelists in this test are selected based on certain criteria. Organoleptic testing involves assessing appearance, aroma, taste and texture using the hedonic method. The results of the panelists' assessments were tabulated using Microsoft Excel and then analyzed descriptively qualitatively. The organoleptic test results showed that beef meatballs with a mixture of A2 carcass meat (DS 1 + DK ¼) received the highest favorability for appearance, aroma, taste and texture with an average score of 5.65. Beef meatballs with formula A2 (DS 1 + DK ¼) are the best meatball products based on organoleptic tests. The conclusions of organoleptic tests and consumer assessments show that the A2 meatball formula (DS 1 + DK ¼) is the best and meets consumer expectations